Validation of the Insightful Leadership Model Based on Organizational Excellence in the Educational System - Badami, Maryam; Jahanian, Ramezan; Mohammadinejad Ganji, Alireza (Assessment and Practice in Educational Sciences, 2024)
The educational system, as one of the key scientific institutions responsible for knowledge production and training individuals, must continually take steps to improve performance and achieve organizational excellence. One of the critical factors influencing organizational excellence within the educational system is the insightful leadership style. The present study aimed to validate the insightful leadership model based on organizational excellence in the educational system. This research was applied in purpose and descriptive-survey in method. The statistical population consisted of all principals of upper secondary schools (girls’ and boys’ schools) in the eight educational districts of Alborz Province, totaling 215 individuals. Based on Cochran’s formula, a sample of 138 participants was determined and selected through simple random sampling. The data collection instrument was a researcher-developed questionnaire comprising six components and 66 items, rated on a five-point Likert scale (from 1 = very low to 5 = very high). Content and face validity of the questionnaire were confirmed using the opinions of academic supervisors and consultants. The reliability of the questionnaire was assessed using Cronbach’s alpha, with coefficients obtained as follows: outcomes = .75, contexts = .71, intervening conditions = .73, causal conditions = .81, strategies = .75, and core category = .80. Data analysis and hypothesis testing were conducted using the structural equation modeling (SEM) approach with AMOS software. The findings indicated that causal conditions, intervening conditions, and contexts had positive and significant effects on the core category, with the strongest influence attributed to contexts followed by causal conditions. Moreover, the core category exerted a positive and significant effect on strategies, and strategies had a positive and significant effect on outcomes.